Factors of staff professionalism at counter services affect customer satisfaction: A case study at TMpoint Jalan Gajah Berang, Melaka / Nurul Akma Ramli and Nurhayati Saliman - Ramli, Nurul Akma; Saliman, Nurhayati (Faculty of Administrative Science and Policy Studies, 2012)
Counter service is the first step before the customer pursue the matter further. Counter services in an organization is important to give first impression for the customer. Instead of that, staff professionalism is very important in fulfilling customer satisfaction. It is mainly because staff professionalism at counter service will deal directly with the customer. Therefore, the purpose of this study was to identify the factor of staff professionalism that will affect customer satisfaction at counter services of TMpoint Jalan Gajah Berang, Melaka. The factors related with this study are communication, emotional management and employees’ competency. The finding in our study shows that all the independent variables which are communication, emotional management and employees’ competency have a significant relationship towards customer satisfaction at counter services. Instead of that, communication is the most significant factor affect customer satisfaction while emotional management is the least factor affect customer satisfaction at counter services.